Evaluation of the Alicyclic Gauche Effect in 2‐Fluorocyclohexanone Analogs: a Combined NMR and DFT Study. Issue 7 (11th February 2020) - Silva, Daniela Rodrigues; Zeoly, Lucas A.; Cormanich, Rodrigo A.; Guerra, Célia Fonseca; Freitas, Matheus P.
Abstract : Herein, we have investigated the effect of an endocyclic group (forming the N–C–C–F fragment) on the conformational preferences of 2‐fluorocyclohexanone analogs. A combined approach of nuclear magnetic resonance and density functional theory calculations was employed to assess the conformational equilibrium in several media. In turn, natural bond orbital analysis and the conformational behavior of other 2‐halocyclohexanone analogs were used to get more insights about the intramolecular interactions governing the conformer stabilities. Our results reveal that any stabilization from interactions featured in the gauche effect is overcome by a short‐range interaction of the fluorine substituent with the carbonyl group. Consequently, the gauche effect in heterocyclic compounds is not as stabilizing as in their acyclic counterparts. Only the electrostatic gauche effect takes place even in polar solvents owing to an attraction between the axial fluorine and an endocyclic quaternary ammonium group. Abstract : The interplay of intramolecular interactions and the effect of an endocyclic group on the conformational preferences of 2‐fluorocyclohexanone analogs are studied. The hyperconjugative fluorine gauche effect could not be observed in heterocycles, while the corresponding electrostatic effect is present even in polar solvents.